2013
DOI: 10.1136/bmjopen-2013-003606
|View full text |Cite
|
Sign up to set email alerts
|

Polytobacco use and multiple-product smoking among a random community sample of African-American adults

Abstract: Objectives:Little is known about polytobacco use among African-American adults. This study is the first to explore this among a random, statewide, community sample of African-American adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 28 publications
2
21
2
Order By: Relevance
“…These findings support existing research which suggests that cigar use is high among African Americans (Cantrell et al, 2013;Kostygina et al, 2014), which is largely due to the high rates of blunt use in this population (Corral, Landrine, Simms, & Bess, 2013;Milam et al, 2013;Montgomery & Oluwoye, in press). Second, the findings also suggested that marijuana and tobacco co-users began smoking cigarettes, cigars and marijuana at a younger age.…”
Section: Discussionsupporting
confidence: 85%
“…These findings support existing research which suggests that cigar use is high among African Americans (Cantrell et al, 2013;Kostygina et al, 2014), which is largely due to the high rates of blunt use in this population (Corral, Landrine, Simms, & Bess, 2013;Milam et al, 2013;Montgomery & Oluwoye, in press). Second, the findings also suggested that marijuana and tobacco co-users began smoking cigarettes, cigars and marijuana at a younger age.…”
Section: Discussionsupporting
confidence: 85%
“…Increased cigar use has been driven by increased use of cigarillos and little cigars among younger, urban, and Hispanic and African-American men 7–9. Typically, little cigar consumers use both cigar product and a conventional cigarette (dual users),9–11 although the epidemiology of US domestic cigar use is obfuscated by multiple definitions of cigar products and the finding that cigar users themselves are uncertain about the classification of the products 10 12. In a recent study of African-American cigarillo (Black & Mild) smokers,13 five unique subgroups were identified that were distinguished by use frequency (daily vs non-daily) and cigar manipulation behaviour (blunts and hyping) as well as flavour choice.…”
Section: Introductionmentioning
confidence: 99%
“…First, we excluded individuals who smoked less than 10 cigarettes per day and/or used other non-cigarette tobacco products. Therefore, our findings may not generalize to a significant portion of the African American smoker population, who are light/intermittent smokers (< 10 cigs/day; Pulvers et al, 2014) and/or are concurrent users of other tobacco products such as small cigars (Corral et al, 2013). We also excluded participants who currently used psychiatric medications, which may limit the generalizability of our findings to individuals with OC symptoms being treated with pharmacotherapy (Pittenger et al, 2005).…”
Section: Discussionmentioning
confidence: 89%